Pemodelan Pola Operasi Sistem Pompa Pada Desain Polder Guna Mitigasi Banjir Dan Rob Di Wilayah Semarang Timur - Rizka Arbaningrum (TEKNIK, 2018)
Floods and robs that often occur in the East Semarang region result in economic, social and environmental losses. In order to improve this condition, permanent handling is needed, namely by making a polder system consisting of sea dikes, retention ponds and pump houses. The purpose of this study was to analyze the modeling of the operational pattern of the pump system in the polder design. The stages of modeling the operational pattern of the pumping system starts from the calculation of flood discharge, modeling of retention ponds, and pumps using HEC-HMS 4.0 software. The next step is analyzing the operational pattern of the pump system. From the results of the study obtained a plan in 25 annual flood discharge for retention ponds is 138 m³ / s. The design of the retention pond is 210 hectares with a depth of 3.7 m. The pump capacity required is 15 m³ / s with a pump composition with a capacity of 2.5 m³ / s and 5 m³ / s, each of 2 units. The pump modeling analysis uses a pump with a capacity of 2.5 m³ / s of 2 units and 5 m³ / s of 6 units. From the results of the analysis show that the operational pattern uses an elevation-discharge function, where the function forms the operational pattern of each pump which will operate based on the water level evaluation criteria for each pump. With these operational patterns, it will reduce operational and maintenance costs